Development of a test bed to investigate conducted and radiated emissions from power line communication networks - Ng, Hock Lee. (2011)
Power Line communications (PLC) also known as Broadband Power Line (BPL) is an economical alternative to communicate over existing power lines. Any communication device would only need to plug a PLC modem into the AC power socket located in the building to gain access to the high-speed internet depending on the speed of the PLC modem or the speed provided by the Internet Service Provider (ISP). Thus, it provides the homeowners or small businesses to use the electrical wiring within their premises without any modification.